Pemberdayaan Pokdarwis melalui Pelatihan Topeng Batik sebagai Upaya Peningkatan Ekonomi di Kampung Emas Plumbungan, Putat, Gunungkidul - Tristanti, Tristanti; Sujarwo, Sujarwo; Pangestuti, Restu; Bhamadewi, Yolanda Donicha; Lajuba, Nukia (Universitas Pahlawan Tuanku Tambusai, 2026)
The 2025 community empowerment partnership scheme service activity was carried out in the form of training in batik mask making for the Kampung Emas Pokdarwis. The objectives of this activity were: 1) to raise awareness among Pokdarwis members of the potential of batik masks in supporting tourism activities in Kampung Emas Plumbungan; 2) to provide Pokdarwis members with knowledge and skills in making batik masks; 3) to provide Pokdarwis members with knowledge and skills in marketing batik masks digitally. The community service activity was carried out in Kampung Emas Plumbungan. The methods used in this activity were lectures, demonstrations, discussions, and hands-on practice. The results of the activity showed that: 1) Pokdarwis is aware of the importance of managing batik masks as a means of supporting tourism activities; 2) Pokdarwis has the knowledge and skills to make batik masks, as evidenced by an increase in the number of motivated Pokdarwis members who have the ability to make batik masks from 5 to 10 people; 3) Pokdarwis has the knowledge and skills to market batik masks online, as evidenced by an increase in sales of 70 masks after the training.